Analisis Pola Penjualan Produk Makanan dan Minuman Menggunakan Algoritma Apriori - Boby; Solikhun; Zulia Almaida Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Sales are seen as a unit of business parameters that are very vital and valuable for business people to manage the business they are running, especially in the cafe business. Cafe Aksara as one of the business actors in the culinary world has a lot of demand in the sale and supply of goods on certain days due to the dynamic nature of visitor patterns and makes business people have to be wiser in setting strategies for the combination pattern of sales of food and beverage products found in Indonesia. Aksara cafe to attract customers. In a process of determining the sales pattern strategy at Cafe Aksara, customers or buyers greatly influence the sales transaction data recorded by the Aksara Cafe business person. However, from the results of these recordings, sales transaction data tend not to be used in a process of determining sales pattern strategies to attract customers and are only used as useless archives for Aksara Cafe business people. From these problems, there are many branches of computer science that can be used as reference points in overcoming sales problems, one of which is the branch of computer science Data Mining. Data Mining is a method that is quite categorical to be recommended in solving problems with the sale of food and beverage products, especially the Apriori Algorithm. The output of the Apriori Algorithm can help Cafe Aksara business people determine sales patterns on the sales data of their products